How Much of Me Do I See in Other Minds? Modulating Egocentricity in Emotion Judgments by tDCS - Anne Weigand; Irene Trilla; Lioba Enk; Garret O’Connell; Kristin Prehn; Timothy R. Brick; Isabel Dziobek (Brain Sciences, 2021)
When inferring the mental states of others, individuals’ judgments are influenced by their own state of mind, an effect often referred to as egocentricity. Self–other differentiation is key for an accurate interpretation of other’s mental states, especially when these differ from one’s own states. It has been suggested that the right supramarginal gyrus (rSMG) is causally involved in overcoming egocentricity in the affective domain. In a double-blind randomized study, 47 healthy adults received anodal (1 mA, 20 min) or sham transcranial direct current stimulation (tDCS) to the rSMG prior to performing a newly developed paradigm, the self–other facial emotion judgment (SOFE) task. In this task, participants made judgments of facial emotional expressions while having been previously confronted with congruent or incongruent emotion-inducing situations. To differentiate between emotional and cognitive egocentricity, participants additionally completed an established visual perspective-taking task. Our results confirmed the occurrence of emotional egocentric biases during the SOFE task. No conclusive evidence of a general role of the rSMG in emotional egocentricity was found. However, active as compared to sham tDCS induced descriptively lower egocentric biases when judging incongruent fearful faces, and stronger biases when judging incongruent happy faces, suggesting emotion-specific tDCS effects on egocentric biases. Further, we found significant tDCS effects on cognitive egocentricity. Results of the present study expanded our understanding of emotional egocentricity and point towards emotion-specific patterns of the underlying functionality.